Media Learning Patch Board in Science Learning Energy Change Materials for Children with Intellectual Disabilities - Juhanaini, J.; Sholihat, Lulu Fikriyah; Maryanti, Rina; Budiman, Rika Aprillia; Armindony, Fandu Fanovanugraha (Indonesian Journal of Teaching in Science, 2022)
The purpose of this study was to determine the use of patch board learning media in science learning about energy changes for children with intellectual disabilities. The method used in this research is one group pretest-posttest. The subjects in this study were children with intellectual disabilities who attended a special school in Indonesia. Children with intellectual disabilities are students at the senior high school level. After learning to use the patch board media, the test results increased. The average initial score obtained through the initial test was 3.75 and then increased to an average of 8. This was because the use of patch board learning media was interesting and easily understood by children. This is also proven that the use of patch board media in science learning materials on energy change can improve the understanding of children with intellectual disabilities, especially in learning science for energy change materials.